HUBUNGAN POLA MAKAN DAN ASUPAN KARBOHIDRAT DENGAN KADAR GLUKOSA DARAH PESERTA PROLANIS DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KOTA SEMARANG - Arolyumna, Anna; mintarsih, Sri Noor (JURNAL RISET GIZI, 2015)
Background : DM prevalence in Indonesia in 2013 was 2.1% while in Semarang City in 2013 the DM cases were ranked second at 10.48% and Kedungmundu Community Health Center was ranked first at 21.55%. One of the factors causing the high prevalence of DM is an unhealthy diet including a high carbohydrate diet, eating fast food habits with high fat content and lack of physical activity Objective: to determine the relationship between diet and carbohydrate intake with PROLANIS participants' blood glucose levels in the working area of Kedungmundu Health Center, Semarang City. Methods: This study included the field of community nutrition with the Cross-sectional method. The number of samples is 33 people. Data collected are blood glucose levels, dietary patterns and carbohydrate intake. The method used is interviews and direct observation. To find out the relationship between variables used the Fisher's Exact Test with a confidence degree of 95%. Results: The results showed that samples with blood glucose levels in the DM category were 48.48%, diet was often as much as 60.61%, and more carbohydrate intake was 21.21%. There is no correlation between diet and glucose levels (p = 0.213). There is no relationship between carbohydrate intake and blood glucose levels (p = 0.271).